A single-center clinical study of hepatic artery variations in laparoscopic pancreaticoduodenectomy: A retrospective analysis of data from 218 cases. Issue 21 (22nd May 2020) - Zhang, Wei; Wang, Kun; Liu, Songyang; Wang, Yingchao; Liu, Kai; Meng, Lingyu; Chen, Qingmin; Jia, Baoxing; Liu, Yahui
Abstract : Abstract: Hepatic artery variations increase the difficulty of laparoscopic pancreaticoduodenectomy (LPD). The safety and efficacy of LPD in the presence of aberrant hepatic arteries (AHA) must be further verified. Patients with normal and variant hepatic arteries who underwent LPD and preoperative arterial angiography were retrospectively analyzed. Variation type, intraoperative management, and clinical treatment outcomes were compared. There were 54 cases (24.8%) of AHA. The most common hepatic artery variation was accessory right hepatic artery (RHA) from the superior mesenteric artery (SMA, n = 12, 5.5%), followed by replaced RHA from the SMA (n = 10, 4.6%), accessory left hepatic artery from the SMA (n = 10, 4.6%), and replaced common hepatic artery from the SMA (n = 6, 2.8%). Each type of arterial variation was successfully preserved in all cases, and there were no significant effects on the evaluated surgical indices, conversion rate, incidence of postoperative complications, or follow-up results. Our findings indicated that preservation of AHAs during total LPD is feasible. There were no significant effects on surgical indices, incidence of postoperative complications, or follow-up outcomes. The influence of AHA on the safety and efficacy of LPD must be further verified. Patients with normal and variant hepatic arteries who underwent LPD and preoperative arterial angiography were retrospectively analyzed. There were 54 cases (24.8%) of AHA. There were no significant effects of AHAs on surgical indices, incidence of postoperative complications, or follow-up outcomes.